2008
DOI: 10.1007/s00011-006-6190-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of inflammatory responses associated with NF-κB pathway in kidneys from diabetic rats

Abstract: Fenofibrate exhibited a downregulating effect on the NF-kappa B pathway in diabetic kidneys, implying that fenofibrate could be a potential treatment for diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Other studies demonstrated that 1,25-dihydroxyvitamin D3 suppresses hyperglycemia-induced gene expression by blocking NF-κB activation in mesangial cells (Zhang et al, 2007). Statins and fenofibrate also exhibit a downregulating effect on NF-κB pathway in kidneys from diabetic rats Chen et al, 2008). In the same way, a recent report demonstrates that the ameliorative effects of the plant alkaloid berberine on renal dysfunction in diabetic rats is associated with its inhibitory function on NF-κB signal pathway in the kidney (Liu et al, 2010).…”
Section: Nf-κbmentioning
confidence: 89%
“…Other studies demonstrated that 1,25-dihydroxyvitamin D3 suppresses hyperglycemia-induced gene expression by blocking NF-κB activation in mesangial cells (Zhang et al, 2007). Statins and fenofibrate also exhibit a downregulating effect on NF-κB pathway in kidneys from diabetic rats Chen et al, 2008). In the same way, a recent report demonstrates that the ameliorative effects of the plant alkaloid berberine on renal dysfunction in diabetic rats is associated with its inhibitory function on NF-κB signal pathway in the kidney (Liu et al, 2010).…”
Section: Nf-κbmentioning
confidence: 89%
“…[71] 3) Thiazolidinedione drugs Ameliorated renal injury in diabetic rats. [73] 4) Statin and fenofibrate down regulates NF-κB [72] 5) Plant alkaloid berberine inhibits NF-κB and ICAM-1 in diabetic rats and ameliorate renal dysfunction [65] From the above study and pathological role it is clear that up regulation of NF-κB in diabetic kidney and plays important role in development of diabetes nephropathy. Thus targeting NF-κB may retard development of nephropathy.…”
Section: Nf-κb Is Inhibited Bymentioning
confidence: 99%
“…NFκB activation triggers potent inflammatory reactions found in acute pancreatitis, DM, metabolic syndrome, brain injury, Alzheimer's disease, and diabetic nephropathy [76]. Into the cortex of the kidneys, NFkB activation was associated with increased expression of plasminogen activator inhibitor-1 (PAI-1) and enhanced expression of the intercellular adhesion molecule-1 (ICAM-1) which were associated with higher degree of renal inflammation in diabetic rats [77]. The activation of p38-MAPK pathway also impairs insulin action into the myocardium increasing free radical-mediated infarction [78].…”
Section: Molecular Pathways Of Diabetes Mellitus Pathogenesismentioning
confidence: 99%